Vγ9Vδ2 T Cells in the Bone Marrow of Myeloma Patients: A Paradigm of Microenvironment-Induced Immune Suppression - Castella, Barbara; Foglietta, Myriam; Riganti, Chiara; Massaia, Massimo (Frontiers in Immunology, 2018)
Vγ9Vδ2 T cells are non-conventional T cells with a natural inclination to recognize and kill cancer cells. Malignant B cells, including myeloma cells, are privileged targets of Vγ9Vδ2 T cells in vitro. However, this inclination is often lost in vivo due to multiple mechanisms mediated by tumor cells and local microenvironment. Multiple myeloma (MM) is a paradigm disease in which anti-tumor immunity is selectively impaired at the tumor site. By interrogating the immune reactivity of bone marrow (BM) Vγ9Vδ2 T cells to phosphoantigens, we have revealed a very early and long-lasting impairment of Vγ9Vδ2 T-cell immune functions which is already detectable in monoclonal gammopathy of undetermined significance (MGUS) and not fully reverted even in clinical remission after autologous stem cell transplantation. Multiple cell subsets [MM cells, myeloid-derived suppressor cells (MDSC), regulatory T cells (Tregs), BM-derived stromal cells (BMSC)] are involved in Vγ9Vδ2 T-cell inhibition via several immune suppressive mechanisms including the redundant expression of multiple immune checkpoints (ICP). This review will address some aspects related to the dynamics of ICP expression in the BM of MM patients in relationship to the disease status (MGUS, diagnosis, remission, relapse) and how this multifaceted ICP expression impairs Vγ9Vδ2 T-cell function. We will also provide some suggestions how to rescue Vγ9Vδ2 T cells from the immune suppression operated by ICP and to recover their anti-MM immune effector functions at the tumor site.